First isolation of rabies virus from a Eurasian badger (Meles meles) in Inner Mongolia, China, 2024 - Chen, Sixu; Bao, Anyu; Aodun, Gerile; Zhang, Pei; Zhang, Lu; Gao, Nan; Qiao, Honglong; Liu, Wenying; Liu, Qiang; Zhang, Yufei (Frontiers in Veterinary Science, 2025)
Rabies continues to pose a significant global zoonotic threat. In recent years, the increased spillover events of rabies viruses from wildlife to domestic animals have raised public health security concerns, prompting heightened international attention toward rabies management in wildlife populations. Our study reveals the first documented case of a rabies virus (RABV) strain isolated from Eurasian badgers (Meles meles) within Chinese ecosystems. Genetic analysis shows 99.4% nucleotide identity with dominant bovine-associated cosmopolitan lineages, offering robust evidence of interspecies transmission from wildlife reservoirs to domestic livestock. It is noteworthy that due to the special geographical location of this region, the habitat of Eurasian badgers overlaps with the territory of livestock and human settlements, thereby forming a transmission chain of rabies virus such as “fox- Eurasian badger-livestock” or “Eurasian badger-livestock.” This critical finding highlights an urgent need for enhanced pathogen surveillance programs in pastoral regions where intensive human-wildlife-livestock interfaces create high-risk transmission zones.